1994
DOI: 10.1002/etc.5620131110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ultraviolet light on the toxicity of sediments contaminated with polycyclic aromatic hydrocarbons

Abstract: Standard 10 d toxicity tests were conducted with freshwater benthic invertebrates using sediments containing a range of concentrations of polycylic aromatic hydrocarbons (PAHs) The assays were performed both under normal laboratory fluorescent light and ultraviolet (UV) light, which mimicked wavelengths present in sunlight, at about 10% of ambient solar intensity In sediments with elevated PAH concentrations, tests conducted with UV light resulted in significantly greater mortality of Hyalella azteca (amphipod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(19 citation statements)
references
References 25 publications
3
15
0
1
Order By: Relevance
“…However, significant light-darkness differences were found for pyrene and fluoranthene (p < 0.05). These observations are in agreement with previous studies where phototoxicity has been shown in a variety of fishes, including bluegill sunfish (Lepomis macrochirus) and fathead minnow (Pimephales promelas) (Ankley et al 1994). In contrast, Kagan et al (1985) did not find toxicity of fluoranthene and pyrene to embryos and larvae of Pimephales promelas.…”
Section: Discussionsupporting
confidence: 93%
“…However, significant light-darkness differences were found for pyrene and fluoranthene (p < 0.05). These observations are in agreement with previous studies where phototoxicity has been shown in a variety of fishes, including bluegill sunfish (Lepomis macrochirus) and fathead minnow (Pimephales promelas) (Ankley et al 1994). In contrast, Kagan et al (1985) did not find toxicity of fluoranthene and pyrene to embryos and larvae of Pimephales promelas.…”
Section: Discussionsupporting
confidence: 93%
“…The U.S. Environmental Protection Agency has identified 16 parent (unsubstituted) PAHs as priority pollutants [5]. Many of these compounds are known toxicants to fish and invertebrates both as parent compounds [6][7][8][9] and photoactivated constituents [10][11][12][13]. Others are sus-* To whom correspondence may be addressed (jbestari@tox.uoguelph.ca).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of UV photoactivation on the toxicity of PAHs is well documented (Zepp, 1979;Bowling et al, 1983;Nikolaou, 1984;Huang, 1993;Ankley, 1994;Gala, 1994;Monson, 1995). PAHs, accumulated in tissue and photoactivated, can damage a cell's proteins, lipids, and DNA.…”
Section: Description and Relevance Of Biomarkersmentioning
confidence: 99%